Exploration of the impact of air pollutants on the influenza epidemic after the emergence of COVID-19: based on Jiangsu Province, China (2020–2024) - Zheng, Chengxi; Jiang, Xin; Yin, Yi; Dai, Qigang; Tang, Shuhan; Hu, Jianli; Bao, Changjun; Yang, Haitao; Peng, Zhihang (Frontiers in Public Health, 2025)
BackgroundNon-pharmaceutical interventions (NPIs) during the COVID-19 pandemic altered influenza transmission patterns, yet the age-specific effects of air pollutants on influenza dynamics remain unclear.MethodsUtilizing influenza surveillance data of Jiangsu Province from 2020 to 2024, we integrated generalized additive quasi-Poisson regression model and distributed lag non-linear models (DLNM) to quantify lagged effects and exposure-response relationships between air pollutants (NO2, SO2, PM2.5) and influenza risk across young, middle-aged, and older adult groups. Meteorological factors, including temperature and humidity, as well as the implementation stages of NPIs, were controlled in the model to isolate the impact of pollutants on influenza transmission.ResultsThe NO2 and SO2 both showed significant positive effects in all age groups. The effect of NO2 is most significant in the young group (RR = 5.02, 95% CI: 4.69–5.37), while SO2 exhibited the most pronounced effects in middle-aged and older adult groups (RR = 4.22, 95% CI: 3.36–5.30; RR = 8.31, 95% CI: 5.77–11.96, respectively). PM2.5 elevated risks in young (RR = 1.99, 95% CI: 1.87–2.12) and older adult (RR = 1.45, 95% CI: 1.07–1.94) groups. Interactions between meteorological factors (temperature, humidity) and pollutants were statistically insignificant.ConclusionsAir pollutant impacts on influenza transmission are age-dependent: NO2 dominates in younger populations, whereas SO2 disproportionately affects older adults. These findings highlight age-related vulnerability to air pollution and the need for targeted public health strategies for different population subgroups.